ÐœÐ¾Ð´Ð¸Ñ„Ð¸ÐºÐ°Ñ†Ð¸Ñ Ð±ÐµÐ»ÐºÐ¾Ð²Ð¾Ð³Ð¾ ÑÐ¾ÑÑ‚Ð°Ð²Ð° Ð¼ÐµÐ¼Ð±Ñ€Ð°Ð½Ð¾-Ñ†Ð¸Ñ‚Ð¾ÑÐºÐµÐ»ÐµÑ‚Ð½Ð¾Ð³Ð¾ ÐºÐ¾Ð¼Ð¿Ð»ÐµÐºÑÐ° ÑÑ€Ð¸Ñ‚Ñ€Ð¾Ñ†Ð¸Ñ‚Ð¾Ð² Ð¿Ð¾Ð´ Ð²Ð»Ð¸ÑÐ½Ð¸ÐµÐ¼ ÐŸÐÐž-1500 - Zubov, P. M.; Zemlyanskikh, N. G.; Babijchuk, L. A. (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2006)
The research purpose was the investigation of protein composition modification in erythrocyte membrane–cytoskeleton complex (MCC) under the effects of non-penetrating cryoprotectant PEO–1500 and the temperature at the contact with high ionic strength solutions and various concentrations of bivalent cations. It was shown that erythrocyte exposure to cryoprotectant solution was accompanied by increase of related content of ankyrin, protein 4.1 and protein 4.2 that probably reflected strengthening vertical links in MCC. The increasing content of protein 4.9 in cells incubated with cryoprotectant could justify of the formation of more rigid actin protofilament structure if compared with intact cells. Strengthening protein–protein interaction in MCC induced in hypertonic PEO–1500 solution can increase erythrocyte mechanic resistance and their stability to cryopreservation. Effect of temperature conditions of erythrocyte incubation with PEO-1500 on protein composition of MCC was poorly expressed.